Nurses' experiences of recruitment and migration from developing countries: a phenomenological approach - Wyness Laura A; Troy Paul H; McAuliffe Eilish (BMC, 2007)
Abstract Background There is growing concern globally at the current flows of nurse migration, particularly from low-income to middle and high-income countries. Recruitment practices of many countries such as Ireland are thought to be fuelling this rate of migration. This paper aims to establish the perceptions and opinions of those involved in the recruitment process on their role in recruitment and the effects recruitment has on both source and destination countries. Methods A purposive sample of 12 directors of nursing, from major academic teaching hospitals in Dublin and hospitals in South Africa and the Philippines were recruited. Ten overseas nurses were also recruited. A phenomenological approach was used with semi-structured interviews as the data collection method. Results There were pronounced differences in opinions between the Irish and the overseas directors on recruitment and its effects on the health systems of the source countries. Difficulties in the retention of staff were highlighted by both groups of directors. Other findings included the language and cultural differences experienced by the overseas nurses. Conclusion Recruitment of overseas nurses should not be left to the individual employer even in the presence of government guidelines. An international effort from all the involved parties is required to formulate a solution to this complex issue in order to protect both the health systems of individual countries and the nurse's right to migrate.